Factors influencing the digital transformation skills of primary school teachers in the southern border province, Vietnam - Trang, Nguyen Ngoc; Phuong, Nguyen Lan (Journal of Education and e-Learning Research, 2023)
The study aims to explore the factors affecting the digital transformation skills of primary school teachers in the southern border province of Vietnam. A descriptive study design was used to collect data from primary school teachers in An Giang province. The survey consists of 25 questions on a 5-level Likert scale designed to collect information on many factors. The primary factor in the digital transformation of teachers is their intention. These findings make practical contributions to the research on the skill development of primary school teachers in the context of digital transformation to improve the quality of education in primary schools. At the same time, the study also provides five factors affecting the digital transformation capacity of primary school teachers, adding additional reference sources to support educational managers in the southern border region of Vietnam in building school development strategies according to the priority levels of each factor.